2021
DOI: 10.4314/ahs.v21i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of transcription factor 7-Like 2 (TCF7L2) gene polymorphism in patients of type 2 diabetes mellitus from Khyber Pakhtunkhwa population of Pakistan

Abstract: Background: Type 2 diabetes mellitus (T2DM) is the most prevalent component of metabolic syndrome. Environmental factors and various complex genes like transcription factor 7-like 2 (TCF7L2) gene have involved in the disease development. Objective: To determine TCF7L2 genetic association (rs7903146C/T and rs12255372G/T) in T2DM patients of Khyber Pakhtunkhwa population of Pakistan. Subjects and methods: This study comprised of 176 subjects including 118 T2DM patients and 58 healthy controls. Genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…They have reported a significant association of rs7903146 with T2DM in all the above populations [ 18 ]. A study on T2DM patients from the Khyber Pakhtunkhwa population showed a significant risk of T allele either in heterozygote or homozygous state [ 19 ]. Similar studies on African, Asian, and Brazilian subjects have reported a strong association of the SNP to T2DM [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have reported a significant association of rs7903146 with T2DM in all the above populations [ 18 ]. A study on T2DM patients from the Khyber Pakhtunkhwa population showed a significant risk of T allele either in heterozygote or homozygous state [ 19 ]. Similar studies on African, Asian, and Brazilian subjects have reported a strong association of the SNP to T2DM [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Replication of case-control studies was carried out in different populations of women with GDM among the rs7903146 [ 25 , 26 , 27 , 28 , 29 , 30 ], rs2237892 [ 31 , 32 , 33 , 34 , 35 ], and rs5219 [ 35 , 36 , 37 , 38 ] SNPs. Meta-analysis studies have been carried out with rs7903146 [ 39 , 40 , 41 , 42 , 43 ], rs2237892 [ 42 , 44 ] and rs5219 SNPs [ 42 ] in women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors are responsible for developing Zn deficiency or can progress to alter the Zn metabolism in liver cirrhosis ( Table 1 ). These factors include insufficient intake alterations in amino acid and protein metabolism, lessened portosystemic shunts, hepatic extraction, impaired absorption due to alcohol influence, and the effects of endotoxins and cytokines, primarily IL-6 [ 63 , 64 ].…”
Section: Deficiency Of Zinc In Liver Diseasesmentioning
confidence: 99%